Overall survival and cancer-specific survival were improved in local treatment of metastatic prostate cancer - Miao, Qi; Wei, Zhihao; Liu, Chenchen; Ye, Yuzhong; Cheng, Gong; Song, Zhengshuai; Chen, Kailei; Zhang, Yunxuan; Chen, Jiawei; Yue, Changjie; Ruan, Hailong; Zhang, Xiaoping (Frontiers in Oncology, 2023)
Abstract Background: For metastatic prostate cancer (mPCa), radical prostatectomy (RP) and radiation therapy (RT) may improve overall survival (OS) and cancer-specific survival (CSS). Compared with RT, RP shows significant advantages in improving patient outcomes. External beam radiation therapy (EBRT) even slightly elevates cancer-specific mortality (CSM) with no statistical difference in OS compared with no local treatment (NLT). Objective: To evaluate OS and CSS after local treatment (LT) (including RP and RT) versus NLT in mPCa. Design, setting, and participants: Within the Surveillance, Epidemiology and End Results (SEER) database (2000-2018), 20098 patients with metastatic prostate cancer were selected in this study, of which 19433 patients had no local treatment, 377 patients with radical prostate treatment, and 288 patients with RT. Outcome measurements and statistical analysis: Multivariable competing risks regression analysis after propensity score matching (PSM) was used to calculate CSM. Multivariable Cox regression analysis was used to identify the risk factors. Kaplan-Meier methods were used to calculate OS. Results: A total of 20098 patients were included. In a competing risk regression analysis after PSM (ratio 1:1), RP resulted in a significantly lower CSM than NLT, while RT showed a slightly lower CSM. In a competing risk regression analysis after PSM (ratio 1:1), RP led to a lower CSM versus RT. As for all-cause mortality (ACM), RP and RT also showed a downward trend. In terms of OS, RP and RT significantly improved the survival probability compared with NLT, with the effect of RP being more pronounced. Obviously, older age, Gleason scores ≥8, AJCC T3-T4 stage, AJCC N1, AJCC M1b-M1c were all associated with higher CSM (P <0.05). The same results held true for ACM. Conclusions: For patients with mPCa, both RP and RT are beneficial to patients, and the efficacy of RP is better than RT from the perspective of CSM and ACM. Older age, higher gleason scores and the more advanced AJCC TNM stage all put patients at higher risk of dying. Patient summary: A large population-based cancer database showed that in addition to first-line therapy (hormonal treatment), RP and radiotherapy can also benefit patients with mPCa.